2019
DOI: 10.1103/physreve.100.020201
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal correlation uncovers characteristic lengths in cardiac tissue

Abstract: Complex spatiotemporal patterns of action potential duration have been shown to occur in many mammalian hearts due to a period-doubling bifurcation that develops with increasing frequency of stimulation. Here, through high-resolution optical mapping and numerical simulations, we quantify voltage length scales in canine ventricles via spatiotemporal correlation analysis as a function of stimulation frequency and during fibrillation. We show that i) length scales can vary from 40 to 20 cm during one to one respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…On the experimental side, fractional diffusion indices have been correlated to the level of heterogeneity in myocardial microstructure through imaging analysis of ex vivo healthy rat ventricles [22], and fractional scaling was shown to characterise spatio-temporal correlation of cardiac electrical properties during paced excitation dynamics through the analysis of optically mapped canine ventricular preparations [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…On the experimental side, fractional diffusion indices have been correlated to the level of heterogeneity in myocardial microstructure through imaging analysis of ex vivo healthy rat ventricles [22], and fractional scaling was shown to characterise spatio-temporal correlation of cardiac electrical properties during paced excitation dynamics through the analysis of optically mapped canine ventricular preparations [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the PGD approximation is less accurate when the transmembrane potential sharply changes. In particular, the error is more significant in the interval [20,22] ms characterizing the wavefront propagation than in the interval [115,120] ms when waveback propagation occurs. This is confirmed by Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the differential equations for the potential propagation in the cardiac tissue is quite consolidated, as witnessed by the specific literature (see, e.g., [14,15,16]). Modeling improvements are mainly devoted to the micro-, meso-and macroscopic (i.e., cell, tissue and organ levels) description of the ions dynamics at cellular and subcellular level [17], to their behavior at the cell-cell interface [18,19], and to the spatio-temporal coupling among the different cardiac components resulting in synchronized emerging phenomena [20]. These models feature parameters that are quite hard to measure in vivo and data assimilation procedures have been recognized as a viable approach [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…These border zones reportedly play a meaningful role in the propagation of action potentials, since they may promote the formation of abnormalities such as action potential alternans 10 and arrhythmias 43 . While recent multiscale models of cardiac tissue have been able to theoretically link the remodelling of gap-junction conductivity with reduced conduction velocity in cardiac tissue 44 , further studies should quantify in biophysical terms the level of remodelling found at the gel-intact tissue interface, in order to incorporate additional nonlinearities in the emerging cardiac behavior 45 48 . Another limitation is the absence of electromechanical coupling in our simulations.…”
Section: Discussionmentioning
confidence: 99%